The intricate diversity of human–nature relations: Evidence from Finland - Raatikainen Kaisa J.; Tupala Anna-Kaisa; Niemelä Riikka; Laulumaa Anna-Mari (Springer Science and Business Media B.V., 2025)
Supporting sustainability requires understanding human–nature relations, which we approached as social constructions that can be studied through nature-related discourses. We examined human–nature relations in Finland by combining approaches from environmental social sciences and arts-based research into a mixed-methods design. A public online survey (n = 726) and post-performance audience interviews (n = 71) portrayed nature positively. Respondents’ ideas of nature ranged from natural scientific to philosophical; from dualistic to holistic; and from ecocentric to anthropocentric. A factor analysis revealed discourses focusing on wellbeing, conservation, ecoanxiety, pro-environmentalism, outdoor activity, and enjoying nature. Interviews added spiritual and over-generational aspects and revealed the importance of embodied experiences in nature relations. We identified dimensions that structure the relations, including human–nature positionality, engagement and contact with nature, and conception and thought. The emotional and experiential aspects, and nature-related practices, deserve further research. We demonstrate how a diversity of human–nature relations co-exists and co-evolves.